First Atlantic satellite tracks of ‘lost years’ green turtles support the importance of the Sargasso Sea as a sea turtle nursery - Mansfield, Katherine L. (Proc Biol Sci, 2021)
In-water behaviour and long-term movements of oceanic-stage juvenile sea turtles are not well described or quantified. This is owing to technological or logistical limitations of tracking small, fast-growing animals across long distances and time periods within marine habitats. Here, we present, to our knowledge, the first long-term offshore tracks of oceanic green turtles (Chelonia mydas) in western North Atlantic waters. Using a tag attachment technique developed specifically for young (less than 1 year old) green turtles, we satellite-tracked 21 oceanic-stage green turtles (less than 19 cm straight carapace length) up to 152 days using small, solar-powered transmitters. We verify that oceanic-stage green turtles: (i) travel to and remain within oceanic waters; (ii) often depart the Gulf Stream and North Atlantic Subtropical Gyre currents, orienting towards waters associated with the Sargasso Sea; (iii) remain at the sea surface, using thermally beneficial habitats that promote growth and survival of young turtles; and (iv) green turtles orient differently compared to same stage loggerhead turtles (Caretta caretta). Combined with satellite tracks of oceanic-stage loggerhead turtles, our work identifies the Sargasso Sea as an important nursery habitat for North Atlantic sea turtles, supporting a growing body of research that suggests oceanic-stage sea turtles are behaviourally more complex than previously assumed.